Positivisation of Islamic Sharia as Local Government Regulations for Minority Citizens as Liyan in Aceh - Helmi Helmi; Nyak Fadhlullah (Department of Government Studies, Universitas Syiah Kuala, 2020)
Although the majority of Aceh's population is Muslim, the rules formulated in the form of Islamic Sharia Qanun cannot be separated from social interaction with non-Muslims as a minority community. This study wants to reveal the position of non-Muslims in Qanun (Sharia rules) for the application of Islamic law in Aceh, with the aim of analyzing how Islamic Sharia Qanun is made and their problems with diverse views on the equality of identity in Aceh. This is based on several facts which show that the paradigm of equality of diverse identities in Aceh has not been a major concern among religious communities. This research is library research using secondary data. Data collection techniques are carried out by reviewing the literature and related documents, namely analyzing 13 Qanun (Sharia Rules) of the application of Islamic Sharia and one Aceh Special Region Regulation, as well as other valid and credible sources. The findings in this library research are the rules formulated in Aceh's Jinayat Qanun giving freedom to the choice of punishment for non-Muslims. This freedom is granted through the principle of surrender, which is regulated in article 129 of Law Number 11 concerning the Government of Aceh and Article 5 of the Aceh Qanun Number 6 of 2014 concerning Jinayat Law.